Collegiate skateboarding in the United States - Peets, Emrys; Ray, Davis; Britt, Takumi; Abramson, Boaz; Anderson, Isabelle; Cubilla, Jesus; Munhoz, Daniel; Sessoms, Monyell; Silva, Thomas; Zen, Bryan (Frontiers in Sports and Active Living, 2025)
Collegiate skateboarding in the United States is experiencing unprecedented growth, fostering inclusive and creative communities that contribute significantly to university culture and student development. This study examines the dynamics of these communities through the National Collegiate Skateboarding Survey (NCSS), with responses from 32 organizations, and corroborative social media analysis. Findings highlight the resourcefulness of skateboarding clubs in navigating institutional barriers, with 41% of clubs reporting conflicts with universities and 28% with law enforcement and 29% of clubs having over 90% male membership, demonstrating persistent gender disparities. Statistical analysis reveals a synergistic relationship between the national rise in skateboarding participation, new club formation, and increased scholarship availability, as indicated by the statistically significant F-statistic of 10.22 (p<0.05). This suggests that collective factors significantly influence scholarship growth, even as individual predictors, such as national participation, lack standalone significance. Beyond challenges, collegiate skateboarding enhances university environments by fostering diverse social connections, artistic expression, and academic engagement, as demonstrated by initiatives like the Collegiate Skateboarding Educational Foundation (CSEF), which has provided 217,000 in scholarships to 109 students between 2018 and 2024. This study highlights the urgent, and growing, need for institutional recognition and support to fully harness the creativity and cultural contributions of skateboarding communities, enabling them to thrive as a dynamic and enriching force within higher education.